2004
DOI: 10.1139/b04-135
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence data and morphology defineCryphonectriaspecies in Europe, China, and Japan

Abstract: Cryphonectria includes important tree pathogens as well as species believed to be saprophytes. Recent phylogenetic studies have concentrated on North American and southern hemisphere Cryphonectria spp., but little is known about Asian and European taxa. In this study we identify and differentiate among the species occurring in Europe, China, and Japan using morphological and phylogenetic comparisons among the Cryphonectria species. Phylogenetic comparisons were based on sequence data from the ribosomal ITS ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…These probes were chosen because they exist as a single copy (nam-1 and b-tubulin gene) or a cluster (ITS) in the genome of C. parasitica and hence can serve to identify specific chromosomes. All probes were prepared by PCR using the total DNA of EP155 as template and primer sets for the respective genes: Nam-7 (5 0 -GCATAGT GAATGGAGCCG-3 0 ) and Nam-49 (5 0 -CAGCCCTGAGTACTTCTCC-3 0 ) for nam-1 (Faruk et al, 2008a), beta-tub7 N (5 0 -GAG GACCA GATGCGCAAC-3 0 ) and beta-tub7C (5 0 -GTGTACCAATGCAA GAAAGCC-3 0 ) for b-tubulin gene (Myburg et al, 2004), and ITS4 (5 0 -TCCTCCGCTTATTGATATGC-3 0 ) and ITS5 (5 0 -GGAAGTAAAAG TCGTAACAAGG-3 0 ) for rDNA (White et al, 1990). Probe labeling, hybridization, and detection of signals were carried out with the PCR DIG synthesis kit (Roche) for all the probes.…”
Section: Southern Blot Hybridizationmentioning
confidence: 99%
“…These probes were chosen because they exist as a single copy (nam-1 and b-tubulin gene) or a cluster (ITS) in the genome of C. parasitica and hence can serve to identify specific chromosomes. All probes were prepared by PCR using the total DNA of EP155 as template and primer sets for the respective genes: Nam-7 (5 0 -GCATAGT GAATGGAGCCG-3 0 ) and Nam-49 (5 0 -CAGCCCTGAGTACTTCTCC-3 0 ) for nam-1 (Faruk et al, 2008a), beta-tub7 N (5 0 -GAG GACCA GATGCGCAAC-3 0 ) and beta-tub7C (5 0 -GTGTACCAATGCAA GAAAGCC-3 0 ) for b-tubulin gene (Myburg et al, 2004), and ITS4 (5 0 -TCCTCCGCTTATTGATATGC-3 0 ) and ITS5 (5 0 -GGAAGTAAAAG TCGTAACAAGG-3 0 ) for rDNA (White et al, 1990). Probe labeling, hybridization, and detection of signals were carried out with the PCR DIG synthesis kit (Roche) for all the probes.…”
Section: Southern Blot Hybridizationmentioning
confidence: 99%
“…& M.J. Wingf. and several related species threaten eucalyptus trees throughout the world (Gryzenhout et al , 2005d (Hoegger et al 2002;Myburg et al 2004) and are often observed in their Endothiella pycnidial states on the exposed roots of hardwood trees.…”
Section: Cryphonectriaceaementioning
confidence: 99%
“…(Lee et al, 1992), although no further studies have been conducted. Firm identification of these Cryphonectria species based on morphology is challenging because the range of spore sizes commonly overlaps and the ascospores are not always fully developed, resulting in variable measurements (Myburg et al, 2004a). In addition, without complete information on the effects of chrysovirus infection on fungal morphology, conclusively identifying abnormal strains of Cryphonectria species based on morphology is even harder.…”
Section: J Microbiolmentioning
confidence: 99%
“…Even though major species of Cryphonectria, such as C. parasitica, C. nitschkei, C. macrospora, and C. radicalis, are known to occur on woody hosts in East Asia (Myburg et al, 2004b), morphological taxonomic identification is still extremely challenging. Therefore, molecular taxonomic studies based on DNA sequence comparisons have been used to resolve many questions (Myburg et al, 2004a).…”
mentioning
confidence: 99%
See 1 more Smart Citation